Roman plasters and mortars from ancient Cosa (Tuscany-Italy). Mineralogical characterisation and construction from domus 10.1 (House with Cryptoporticus) - Moreno Alcaide, Manuel; Compaña Prieto, José Manuel (Elsevier, 2018)
Between 2005 and 2012, we worked on the project «La ciudad romana de Cosa: arqueología de un enclave comercial mediterráneo» supported by Spanish Goverment. The excavation campaigns carried out since 2005 have made it possible to learn the architect's plan of the House 10.1 (House with Cryptoporticus). The present work aims to provide a study of the construction techniques as well as analytical support to gain knowledge of the plasters and mortars of the main rooms, tablinum and peristylum, of the domus 10.1 of Cosa (House with Cryptoporticus). For the study of the plasters and mortars, two different analytical techniques were used to determine its composition: optical stereo microscope and polarized light microscopy.
Keywords: Yeso (Material) - Cosa (ciudad romana); Arqueología clásica; Roman plaster; Roman Archaeology